Effects of Colletotrichum gloespororiodes and Monilinia fructicola on quality of red flesh dragon fruit (Hylocereus polyrhizus). - Awang, Yahya; Abdul Ghani, Muhd Azlan; Sijam, Kamaruzaman (International Society for Horticultural Science, 2010)
Colletotrichum gloeosporioides and Monilinia fructicola have been identified as important pathogenic fungi of dragon fruit in Malaysia. Based on external appearance, fruit are unlikely to be acceptable a few days after infection. A study was conducted to examine changes in several fruit quality attributes of red flesh dragon fruit (Hylocereus polyrhizhus) following inoculation with C. gloeosporioides and M. fructicola at two spore concentrations (104 and 106 spores ml-1). Three days after inoculation, disease symptoms were apparent on fruit inoculated with C. gloeosporioides at both spore concentrations while fruits inoculated with M. fructicola were only infected at a concentration of 106 spores ml-1. At 106 spores ml-1, lesions caused by M. fructicola were larger than those caused by C. gloeosporioides. Once infected, fruit quality was markedly reduced but the magnitude of the effect was dependent on spore concentration. Fruit soluble solids content decreased from 8.9% in uninoculated control fruits to 6.0 and 6.1, respectively in C. gloeosporioides and M. fructicola inoculated fruits (106 spores ml-1), while titratable acidity was reduced from 0.11 to 0.06% under similar conditions.